PENGARUH DEBT TO EQUITY RATIO, NET PROFIT MARGIN DAN TOTAL ASSET TURNOVER TERHADAP NILAI PERUSAHAAN PADA PT. NIPPON INDOSARI CORPINDO TBK PERIODE 2013-2023 - Fernanda Septiana, Ana; Elfahmi, Ryan (Journal of Research and Publication Innovation, 2024)
This study aims to determine the Effect of Debt to Equity Ratio, Net Profit Margin and Total Asset Turnover on Company Value at PT Nippon Indosari Corpindo Tbk for the 2013-2023 Period. The method used in this study is to use a quantitative method with several data analysis techniques including Descriptive Statistical Test, Classical Assumption Test, Model Feasibility Test, Multiple Linear Regression Analysis, and t Hypothesis Testing using SPSS software version 26. The results of this study indicate that Debt to Equity Ratio has an effect on Price to Book Value, this is evidenced by the results of the hypothesis test (t-test), Debt to Equity Ratio has a t count value of 5.845> t table 2.365 and a significance value of 0.001 <0.05. Net Profit Margin does not affect Price to Book Value, this is proven by the results of hypothesis testing (t-test), Net Profit Margin has a calculated t value of -0.885 <t table -2.365 and a significance value of 0.405>0.05. Then the results of the Total Asset Turnover study do not affect Price to Book Value, this is proven by the results of hypothesis testing (t-test), Total Asset Turnover has a calculated t value of 1.165 <t table 2.365 and a significance value of 0.282> 0.05. Then the Debt to Equity Ratio, Net Profit Margin and Total Asset Turnover influence Price to Book Value, this is proven by the results of simultaneous testing (f-test), the f count value is 24,927 > f table 4,35 and the significance value is 0,000 < 0,05.